Manajemen Pembelajaran Tahfidz di Sekolah Menengah Pertama Khairunnas Malang - Sulaichah, Sulaichah; Purbaningrum, Endang; Sholeh, Muhamad (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
This research was carried out against a background of high interest in parents enrolling their sons and daughters in the Tahfidz Al Qur'an Islamic Boarding School and high interest in students who wish to have the goal of becoming hafidz Qur'an because of the glory that Allah has bestowed upon the guardians of the Qur'an. This study aims to: (1) Describe the learning management plan for tahfidz Al-Qur'an learning at SMP Khairunnas Malang. (2) Describe the implementation of tahfidz learning management at SMP Khairunnas Malang. (3) Describe the evaluation of learning tahfidz Al Qur'an. (4) Describe the inhibiting factors for the implementation of tahfidz Al-Qur'an learning. The research method used is descriptive qualitative approach. Data collection techniques using interviews, observation, and documentation. Data validity uses data and source triangulation. Data analysis used interactive methods and consisted of data reduction, data presentation and drawing conclusions. The results of this study show that: (1) the learning management plan for tahfidz Al Qur'an learning at SMP Khairunnas Malang has been formulated clearly by determining the learning objectives for tahfidz Al Qur'an to improve school quality; set standards for learning tahfidz Al Qur'an; build good cooperation with school principals, heads of Al-Qur'an programs, teachers, students and parents to achieve targets and maximum results; compiling steps for learning the Qur'an; compiling learning tools for tahfidz Al Qur'an. (2) The management of learning the tahfidz of the Qur'an at SMP Khairunnas Malang is carried out through preliminary activities, core activities and closing activities. So that preparation in learning activities can be conveyed in accordance with what has been planned. (3) Organizing the management of tahfidz learning at SMP Khairunnas Malang is carried out by assembling a team of reference learning tools, making mutabaah books or memorization achievements, making reports on students' tahfidz learning outcomes and overseeing good and quality tahfidz learning. (4) Evaluation of the management of learning tahfidz Al Qur'an at SMP Khairunnas Malang is carried out by the Principal and Head of the Tahfidz Al Qur'an Program in the form of upgrading and supervising activities in learning tahfidz Al Qur'an; carry out the assessment mechanism for learning Al-Qur'an tahfidz at SMP Khairunnas Malang according to the stages; and make a report book on the results of learning tahfidz Al Qur'an (raport).